Oxidation-affected erosion of porous Ni-Al intermetallic alloy in combustion applications: Pore-scale simulation - Yakovlev, Igor A.; Astakhov, Daniil; Zambalov, Sergey D.; Pichugin, Nikita; Maznoy, Anatoly (Metals)
Advanced high-temperature oxidation resistance is a crucial characteristic of metallic materials in porous burners. Extreme combustion conditions could lead to oxidation-affected erosion of porous media at a long-time period of burner operation. In this paper, we numerically simulated oxide scale growth at a porous radiant burner fabricated by Ni-Al intermetallic alloy using the combustion synthesis method, focusing on the structure degradation caused by periodic oxide scale spallation. A three-dimensional geometrical model of a porous intermetallic scaffold was obtained by scanning the porous burner using the X-ray CT technique. The surface erosion was modeled by the surface reconstruction based on calculated values of spalled oxide layer thickness. The simulation revealed that the submerged flame results in non-uniform distribution of the temperature at the solid surface. Such non-isothermal conditions lead to a two-times thicker oxide scale at the external surface of the burner. Thin struts of the intermetallic scaffold are prone to oxidation-affected erosion first, which forms discontinues and further fragmentation. The porous scaffold could lose about 50% of initial weight before fragmentation under conditions with intense oxide spallation. In such large structural degradation, the average flow velocity could reduce by a factor of 3, leading to changing of flame stabilization region